Correlation between Survival and Tumour Characteristics in Patients with Chondrosarcoma. (December 2015) - Kamal, Achmad Fauzi; Husodo, Kurniadi; Prabowo, Yogi; Hutagalung, Errol Untung
Purpose: To evaluate the correlation between survival and tumour characteristics in 23 patients with chondrosarcoma. Methods: Records of 15 men and 8 women aged 14 to 66 (mean, 37) years who were diagnosed with primary (n=19) or secondary (n=4) chondrosarcoma of the axial skeleton (n=8), proximal extremity (n=9), or distal extremity (n=6) were reviewed. The tumour diameter was <10 cm in 4 patients, 10–19 cm in 12, and 20–30 cm in 7. The tumour involved the intramedullary in 17 and the periosteum in 6 patients; tumour extension was intracompartmental in 5 and extracompartmental in 18 patients. The Evans histological grade for the tumours was grade 1 in 6 patients, grade 2 in 10, and grade 3 in 7. The mean tumour size was 12.3 cm for grade 1 tumours, 18.2 cm for grade 2 tumours, and 18.3 cm for grade 3 tumours. 13 patients had no metastasis and 3 of 10 patients with grade 2 tumours and all 7 patients with grade 3 tumours had metastasis to the lung at presentation. 17 patients underwent surgery, one underwent adjuvant treatment only, and 5 declined treatment. Results: The mean follow-up period for the 23 patients was 3.1 years (range, 3 weeks to 9 years). The 5-year survival rate was 43% overall, 83.3% for grade 1 tumours, 50% for grade 2 tumours, and 0% for grade 3 tumours. The median survival duration was 20 (95% confidence interval, 11–29) months. Two patients had local recurrence and 16 did not, and the 5 patients who declined treatment died. Survival correlated with Evans histological grading (p=0.004), the presence of metastasis at presentation (p=0.026) and local recurrence (p=0.004). Conclusion: The survival rate was lower in patients with higher Evan grading, metastasis, or local recurrence.